2021
DOI: 10.1016/j.radcr.2021.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian vein thrombosis as a first manifestation of COVID-19 infection

Abstract: COVID-19 infection is associated with high risk of venous thromboembolic events mainly pulmonary embolism or deep venous thrombosis of the lower limbs. Ovarian vein thrombosis is a rare and serious condition usually seen in the immediate postpartum period and other conditions including pelvic inflammatory diseases, gynecological malignancies, hypercoaguable states and few cases to date have reported ovarian vein thrombosis as a complication of COVID-19 infection. Patient with ovarian vein thrombosis usually pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Symptomatic postpartum OVT occurs in 0.01-0.05% of deliveries, especially in C-sections [17]. In this review, no significant obstetric history was found in the majority of the cases (77.77%) [6,11,13,14,[18][19][20].…”
Section: Patient Demographicsmentioning
confidence: 68%
See 2 more Smart Citations
“…Symptomatic postpartum OVT occurs in 0.01-0.05% of deliveries, especially in C-sections [17]. In this review, no significant obstetric history was found in the majority of the cases (77.77%) [6,11,13,14,[18][19][20].…”
Section: Patient Demographicsmentioning
confidence: 68%
“…Our review corroborates a similar finding. A total of 66.66% of patients presented within the first two weeks after a COVID-positive test [11,13,[18][19][20][21]. The remaining 33.33% of patients took three to eight weeks for presentation [6,14].…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both small and large vessel thrombosis has been reported in patients with COVID-19 [16,17]. Published reports have mentioned VSM, PV, aortic, hepatic artery, splanchnic vein, portomensenteric and ovarian vein thrombosis as a result of the hypercoagulable state due COVID-19 [2,16,[18][19][20][21][22][23][24][25][26]. The digestive manifestations of a SARS-CoV-2 infection are varied and nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy study by Wichmann et al reported microthrombi in the prostate of male patients [38] . In female COVID-19 patients, there were also reports of primary ovarian failure (POF) and ovarian vein thrombosis (OVT) [187] , [188] , [189] , [190] , [191] . One study reported POF due to long COVID-19 [192] , and another presented a case of OVT in a pregnant woman [193] .…”
Section: Introductionmentioning
confidence: 99%